Clipado Microquirúrgico de Aneurismas del Segmento A1: Anatomía y estrategias quirúrgicas - Baldoncini, Matias (Revista Argentina de Neurocirugía, 2021)
Introduction:Aneurysms originating from the proximal segment of the anterior cerebral artery are extremely rare. The objective of the following work is the analysis of the anatomy of the anterior cerebral artery in its A1 segment, describing the surgical strategies in two patients.Material and Methods:In a formalized adult head, a right pterional approach and dissection of the Sylvian fissure were performed, exposing the main vascular structures. Two young patients operated on for aneurysms in the anterior cerebral artery, segment A1, are also presented.Results:In the anatomical laboratory work, the vascular structures were exposed, especially detailing the A1 segment of the anterior cerebral artery and its collateral branches. Correct microsurgical clipping was achieved in both patients, with complete occlusion of the aneurysm and good postoperative results.Discussion:Some of the characteristics of these aneurysms that differentiate them from the rest are the perforating arteries that surround them, the risk of rupture in small sizes, the variants and vascular anomalies, among others. Depending on the projection of the aneurysm and its relationship with the lenticulostriate arteries, the best path for clipping must be chosen between the vascular angles in the area.Conclusions:Adequate preoperative anatomical location and surgical planning are the key to the successful management of this pathology.
Keywords: Microsurgery, Neuroanatomy, A1 Aneurysms, Vascular Surgery